The Role of National Courts in International Arbitration - Grimmer, Sarah (Victoria University of Wellington Law Review, 2024)
International arbitration has long been the preferred method of resolving cross-border disputes. While parties to an arbitration agreement made a conscious decision to exclude court jurisdiction, the role of the national courts in supporting the international arbitration process is critical. Through a discussion of recent investment treaty arbitration cases, this article explores the ways in which courts support the international arbitration process, with a focus on the courts' power to review tribunals' findings on jurisdiction, both positive and negative. It reveals how impactful the choice of the seat of arbitration is as determinative of the law that courts must apply to the arbitration procedure.